Hubungan Respon Time Perawat Dengan Kepuasan Pasien Di Instalasi Rawat Jalan RS X - Istikomah , Lutfi Riskyta; Hutahaean, Serri (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2023)
Response time is the time in receiving health services when the patient registers until he arrives at the polyclinic and is checked by the nurse quickly and accurately. Response time can affect patient satisfaction based on the fulfillment of health services. This study aims to determine The Relationship between Nurse Response Time to Patients in the Outpatient Installation of Budhi Asih Hospital. The research design used a descriptive-analytic design with the cross-sectional method. The sampling technique in this study used accidental sampling with 170 respondents as a sample of patients in outpatient installations, namely internal medicine, surgery, and pulmonary polyclinics. The instruments used are questionnaires and nurse response time observation sheets and patient satisfaction questionnaires. Response Time of nurses as many as 92 respondents (54.1%) was